DESIGNING SOCIO-CULTURAL TECHNOLOGIES IN THE TRANSFORMATION OF SOCIETY (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the importance of designing socio-cultural technologies in the transformation of society is studied, divided into types such as political, cultural and social design. In particular, social planning is a type of activity, which is directly related to the development of the social sphere, includes the issues of organizing the effectiveness of social work, eliminating various social problems, and has been studied socio-philosophically. The social policy of the state cannot be imagined without the use of design technologies, the effectiveness of such activities in society is well demonstrated in the practice of many countries.